Well Integrity Management: A Recommendation for Indonesia's Well Life Cycle - Ganesha R Darmawan (Journal of Earth Energy Engineering, 2021)
Indonesia oil and gas field mostly are brownfields which were drilled in the late '40s up to '90s. Development and further development of a new structure throughout the years is done, including drilling exploration wells with new play and development wells. Now, most well locations become a populated village and might raise the potential risk to the people and environment. To fulfil safety commitment, well production operations have to be done safely to the people and environment. Currently, there are no specific data that has registered all the wells in Indonesia. This issue is critical for Government and the operating companies to prepare for abandonment waves to prevent methane emissions from abandoned wells. Well Integrity Management, including well registering/database, reporting, risk assessment of trouble wells, and way forward for all the wells, should be initiated by the Government to ensure integrity assurance. It aims to prevent unwanted event in the future, including when the well is permanently abandoned. This paper will present literature studies about international well integrity standards and how well integrity manages the well life cycle. This paper is also providing recommendation to implement Well Integrity Management in Indonesia to ensure end to end well register.